FINGERPRINT BASED DOOR SECURITY SYSTEM PROTOTYPE USING THE MINUTIAE METHOD (Case Study: Lhokseumawe State Polytechnic ICT Department Laboratory) - Muhammad Nofrizal; Azhar; Hendrawaty (Bulletin of Engineering Science, Technology and Industry, 2024)
Laboratory security is a very important thing to pay attention to and to create laboratory security there are many things to do, one of which is by utilizing technology to maintain the security of the laboratory because lecturers often store very important items and archives in the laboratory. Security using conventional keys or using manual keys which are widely used by teaching staff or lecturers is easily disabled by criminals. Therefore, technology is needed that can be used to increase security, one of which is fingerprint scanning. System design is carried out through designing Flowcharts, Block Diagram Systems and Data Flow Diagrams. This system was built using the C++ and PHP programming language using the Fingerprint module which has the Minutiae method available in it. When using this system, the fingerprint that is scanned will check the ID into the database. If the ID is correct and meets the requirements to unlock the door, the lock on the door will open. The output result of this system is that this system can work in real time by sending the finger ID and laboratory ID to the webserver for checking, the selenoid lock on this system can also be opened with a push button and on the fingerprint sensor there is a minutiae method for extracting and matching fingerprints. automatically.